Fatores de riscos associados à mortalidade de pacientes com Covid-19 submetidos à ventilação mecânica invasiva em um hospital no Nordeste do Brasil - Freitas, Francisco Cleiton Ribeiro (2024)
The COVID-19 pandemic emerged at the end of 2019. Since then, a large part of the world's population has been affected by this disease. Understanding the dynamics of the factors that influence the mortality of critically ill patients on invasive mechanical ventilation (IMV) is very important for better management of these individuals. This can minimize the risk of unfavorable outcomes. Although Brazil has a unified health system, which provides universal health coverage, there are differences in the capacity of the health system between regions. The aim of this study was to assess the factors associated with the death of patients with COVID-19 who underwent invasive mechanical ventilation in a hospital in northeastern Brazil. This is a retrospective cohort study of patients hospitalized for COVID-19 who underwent invasive mechanical ventilation at the São José Hospital for Infectious Diseases in Fortaleza, Ceará. Individuals admitted to intensive care units (ICUs) between May 2020 and December 2021 were included. Data was collected by reviewing medical records. The primary outcome was death during hospitalization. Clinical, epidemiological, laboratory and ventilatory variables were investigated. Statistical analysis was carried out using STATA 13.0. A p-value < 0.05 was considered significant. A total of 228 patients were included in the study; 62.7% were male, and 81.6% had another previous illness. In 2020, patients affected by COVID-19 had higher mean lymphocytes (1050 vs. 800 cells/mm3 ; p = 0.003), sodium (139.7 vs. 136.5 mEq/L; p = 0.000), potassium (4.1 vs. 3.8 mEq/L; p = 0.001), urea (62 vs. 50.5 mg/dL; p = 0.030) and creatinine (1.6 vs. 1.1 mg/dL; p = 0.009). However, a lower average hemoglobin (12.6 vs. 13.4 g/dL; p = 0.001) was observed in these individuals when compared to patients in 2021. Of all the patients admitted, 70.6% were already using supplementary oxygen on admission. After using IMV, 67.1% of patients were placed in the prone position, and 88.2% had some complication during their ICU stay. The overall mortality rate was 49.5%. In the bivariate analysis, the factors associated with mortality were age ≥ 60 years (RR 1.56 CI 95% 1.20 - 2.03; p=0.001), diabetes mellitus (RR 1.33 CI 95% 1.02 - 1.74; p=0.052), hemoglobin < 10 g/dL (RR 1.65 CI 95% 1.21 - 2.24; p=0.029), creatinine ≥ 1.3 mg/dL (RR 1.52 95% CI 1.18 - 1.95; p=0.003), and lactate dehydrogenase ≥ 500 U/L (RR 1.45 95% CI 1.11 - 1.89; p=0.006), oxygenation level < 100 pre-intubation (RR 1.84 95% CI 1.23 - 2.77; p=0.001. Ventilatory and arterial blood gas parameters and pulmonary mechanics were also factors associated with mortality. In the Poisson regression analysis, the independent risk factors were tidal volume >6 ml/kg (RR 1.79 95% CI 1.29 - 2.46, p=0.000), distension pressure ≥ 15 cmH2O (RR 1, 76 95% CI 1.06 - 2.95, p=0.030) at 48 hours of IMV, use of vasoactive drugs (RR 2.62 95% CI 1.04 - 6.59, p=0.041), and hemodialysis (RR 1.49 95% CI 1.07 - 2.07, p= 0.017). ICU length of stay ≥ 10 days (RR 0.72 95% CI 0.56 - 0.93, p=0.011) was a protective factor. Our findings show that critically ill COVID-19 patients with a greater number of organ dysfunctions and those who did not maintain a protective mechanical ventilation strategy were the individuals most at risk of death.